2022
DOI: 10.1007/s00103-022-03617-9
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitsinformationsverhalten und Gesundheitskompetenzen zur COVID-19-Schutzimpfung von Menschen in Deutschland – Befunde der CoSiD-Studie

Abstract: Zusammenfassung Hintergrund Obwohl die COVID-19-Schutzimpfung schwere Krankheitsverläufe sowie Hospitalisierungen und Todesfälle reduziert, ist jede vierte bis fünfte Person in Deutschland nicht gegen COVID-19 geimpft. Um diese Menschen zu erreichen, werden effektive Informations- und Kommunikationsmaßnahmen benötigt. Dafür ist es wichtig, den subjektiven Informationsstand, das Informationsverhalten sowie die Gesundheitskompetenzen im Bereich der COVID-19-Schutzimpfung insbesondere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
3
0
3
Order By: Relevance
“…Our study found that more frequent COVID‐19 information‐seeking and higher COVID‐19 health literacy were indirectly associated with positive intentions for vaccination. These findings are consistent with previous research on COVID‐19 vaccination 16 , 17 , 18 , 19 and highlight the importance of caregivers' health literacy in understanding the risks and benefits of vaccination and making informed decisions for their children. Given the extensive media coverage and conflicting information surrounding COVID‐19 vaccines, individuals with lower COVID‐19 health literacy may have difficulty distinguishing accurate information from myths or misinformation, leading to lower vaccination intentions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that more frequent COVID‐19 information‐seeking and higher COVID‐19 health literacy were indirectly associated with positive intentions for vaccination. These findings are consistent with previous research on COVID‐19 vaccination 16 , 17 , 18 , 19 and highlight the importance of caregivers' health literacy in understanding the risks and benefits of vaccination and making informed decisions for their children. Given the extensive media coverage and conflicting information surrounding COVID‐19 vaccines, individuals with lower COVID‐19 health literacy may have difficulty distinguishing accurate information from myths or misinformation, leading to lower vaccination intentions.…”
Section: Discussionsupporting
confidence: 90%
“… 13 , 14 The relationship between health literacy and vaccination acceptance is unclear, with different studies showing contrasting results. 15 Recent studies addressing the relationship between health literacy and COVID‐19 vaccination found lower health literacy is associated with lower vaccine uptake 16 , 17 , 18 , 19 and results in higher vaccination hesitancy by mediating the effect of distrust 20 or with the moderating role of stress. 21 Data on caregivers' decision to vaccinate young CCS against COVID‐19 is scarce, and the current study seeks to fill this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Bosle et al. 2022 ; Hugger 2021 ; Schäfer 2021 ). Subjektive Einstellungen zu Medien- und Informationsquellen (vgl.…”
Section: Einflussfaktoren Beim Impfen: Die Rolle Des Informationsverh...unclassified
“…In 2021, three representative surveys (called "Kommunikation der Corona-Schutzimpfung in Deutschland" (CoSiD; regarding representativeness, please see [15]) of the general population (i.e., the German-speaking population aged 16 and older) and particular subgroups (such as individuals aged 66 and over as well as medical professionals with patient contact) were conducted by the Federal Centre for Health Education ("Bundeszentrale für gesundheitliche Aufklärung", BZgA). COVID-19 immunization (in terms of knowledge level, attitudes, and behavior) was the main subject of the CoSiD study.…”
Section: Samplementioning
confidence: 99%